Analysis of extrachromosomal structures containing human centromeric alphoid satellite DNA sequences in mouse cells. - Taylor, S; Larin, Z; Tyler-Smith, C (1996)
Yeast artificial chromosomes (YACs) spanning the centromeric region of the human Y chromosome were introduced into mouse LA-9 cells by spheroplast fusion in order to determine whether they would form mammalian artificial chromosomes. In about 50% of the cell lines generated, the YAC DNA was associated with circular extrachromosomal structures. These episomes were only present in a proportion of the cells, usually at high copy number, and were lost rapidly in the absence of selection. These observations suggest that, despite the presence of centromeric sequences, the structures were not segregating efficiently and thus were not forming artificial chromosomes. However, extrachromosomal structures containing alphoid DNA appeared cytogenetically smaller than those lacking it, as long as yeast DNA was also absent. This suggests that alphoid DNA can generate the condensed chromatin structure at the centromere.